Pregnancy outcome in women after total hip replacement: A population-based study. (July 2019) - Kuitunen, Ilari; Artama, Miia; Eskelinen, Antti; Skyttä, Eerik T.; Huhtala, Heini; Uotila, Jukka
Abstract: Objective: Only a few small studies have been published on pregnancies after total hip replacement (THR), and they have reported no adverse pregnancy outcomes after THR. The aim of our study was to evaluate whether maternal THR affects pregnancy outcomes on a population-based level. Study Design: Data for this nationwide register-based cohort study have been collected from four national registries in Finland from 1980 to 2007. All females who had undergone THR during that period formed the patient group, and three controls for each patient without THR were selected. Patient group comprised 2429 women, 719 (29.6%) of whom had 1190 pregnancies ending in singleton deliveries. Of those births, 986 were before THR and 204 after THR. The control group comprised 7276 women, 2805 (38.6%) of whom had 5112 pregnancies ending in singleton deliveries, 3695 occurred before the index date (time point when THR took place within the patient group) and 1417 after. Logistic regression model was used to analyze univariable and adjusted odds ratios (aOR) for adverse neonatal outcomes after maternal THR compared with controls. Data were adjusted using the following variables: maternal age, smoking, rheumatoid arthritis. Results: Stillbirth was more common in the patient group compared with control group 4 (2.0%) vs 8 (0.6%) p = 0.02. Moreover, neonates in the patient group were more likely to be born preterm (aOR 3.58, p=<0.001), small for gestational age (aOR 2.83, p = 0.006) and low birthweight (aOR 4.79, p=<0.001), compared to control group. Trial of labor more likely ended in emergency cesarean section in the patient group than in the control group 39 (28.9%) vs 150 (11.6%), p=<0.001. Adverse pregnancy outcome was more common after THR also when compared to pregnancies before THR. Conclusions: Neonates born after maternal total hip replacement have an increased risk of stillbirth, small for gestational age, low birthweight and preterm birth. Trial of labor is more likely to end in emergency cesarean section.